Corrosion Resistance of Graphene-Reinforced Waterborne Epoxy Coatings. Issue 5 (May 2016) - Liu, Shuan; Gu, Lin; Zhao, Haichao; Chen, Jianmin; Yu, Haibin
Abstract : Graphene (G) was dispersed uniformly in water and used as an inhibitor in waterborne epoxy coatings. The effect of dispersed G on anticorrosion performance of epoxy coatings was evaluated. The composite coatings displayed outstanding barrier properties against H2 O molecule compared to the neat epoxy coating. Open circuit potential (OCP), Tafel and electrochemical impedance spectroscopy (EIS) analysis confirmed that the corrosion rate exhibited by composite coatings with 0.5 wt% G was an order of magnitude lower than that of neat epoxy coating. Salt spray test results revealed superior corrosion resistance offered by the composite coating.